Bones and the dog gone mystery - Adler, David A.; Newman, Barbara Johansen (Puffin Young Readers New York, 2008)
While looking for his lost magnifying glass in the park, young Detective Jeffrey Bones and his grandfather discover that Curly the detective dog is missing, too, and start tracking down clues